Salivary Alpha-amylase Assessment of Pre-Event Anxiety Profiles among University Combative Sports Athletes Proximal to Competition - Honawon, Nunayon Philip; Okuneye , Rafiu; Lawal , Olufemi; Sunmonu , Mathew; Adesanya, Adeyemi; Oyekunle , Abimbola (Journal of Educational Sciences, 2025)
This study assessed the pre-event anxiety profiles through the use of salivary alpha-amylase in university combative sports athletes proximal to competition to inform effective personalized psychological interventions tailored to sport and gender. Fourteen (14) university athletes, 7 boxers (M=34.23, SD=5.96) and 7 judokas (M=34.91, SD=4.17) with Age M = 21.29 voluntarily participated in the study. Saliva samples were collected at two time points, 2 months apart at 9:00 a.m., to control for diurnal cortisol variation, and analyzed using the ELISA protocol. T-tests and ANCOVA were used to determine statistical significance at the 0.05 level. Results showed that salivary alpha-amylase can significantly assess the pre-event anxiety profile (f=1, 48.84, p < .05) of university combative sports athletes, with no significant gender-based differences between genders [t (12) = -0.24, p > .05] or sports-based difference [t (6.68) = 1.47, p > .05]. Although judokas and female athletes had higher mean sAA levels than boxers and male athletes. Sport psychologists and coaches are admonished to use salivary alpha-amylase monitoring in conjunction with psychological assessments to create customised arousal regulation strategies for individual pre-event anxiety responses, with particular attention to subtle sport- and gender-related physiological trends.